Acquired Coagulopathies Secondary to Plasma Cell Dyscrasias: A Report of Two Cases and Review of Literature - Diljith, Hitha; Pagadalu, Ambika Lokababu; Jinkala, Sreerekha; Kar, Rakhee; Jacob, Sajini Elizabeth; Basu, Debdatta (Annals of Pathology and Laboratory Medicine, 2019)
We report hemostatic dysfunction in two postmenopausal women presenting with mucosal bleeds secondary to plasma cell dyscrasias. The two postmenopausal women presented with complaints of mucosal bleeds like gum bleed and epistaxis. Peripheral smear examination showed rouleaux formation. After detailed haematological and coagulation work up, one patient was diagnosed as WaldenstroÂ¨m macroglobulinemia (WM) with acquired vWD and impaired platelet function. The second patient was diagnosed as Multiple myeloma (MM) with acquired coagulopathy. Evaluation of elderly patients with bleeding manifestations should also include work up ruling out an acquired coagulation abnormality secondary to plasma cell dyscracia.